Estimation of forces and moments of lower limb joints from kinematics data and inertial properties of the body by using inverse dynamics technique - Chowdhury, S.; Kumar, N. (Journal of Rehabilitation Robotics, 2013)
In this paper, the forces and its moments acting on hip, knee & ankle joints of the body have been estimated with the help of kinetic models for better biomechanics understanding of human gait. This helps in accurate measurement of segmental masses, acceleration, joint centers and moment of inertia acting at various joints. Free Body Diagram (FBD) and Link Segment Model (LSM) are used for computing forces & moments using Inverse Dynamics (ID) technique. Available lower limb walking model is limited in terms of number of joint forces and moments are analyzed; so, the improved biomechanical model for kinetic analysis of human walk involving lower limb joints & muscles is proposed which estimate the forces acting on the hip joint, knee joint & ankle joints. This was also performed to understand the cause of deviation in any movement by estimating the patterns of forces acting on lower limb joints. Result analysis provides input parameter for the development of prosthetic foot design. by informing the force and moment values of lower limb joints. This analysis will also help for quantification of lower limb prosthetics.